2006
DOI: 10.1007/s10508-005-9001-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Arousal in Women with Superficial Dyspareunia

Abstract: The role of sexual arousal in the etiology and/or maintenance of superficial dyspareunia is still unclear. Lack of sexual arousal may be both the cause and the result of anticipated pain. This study compared genital and subjective sexual responses to visual sexual stimuli of women with dyspareunia and women without sexual complaints. We investigated whether women with dyspareunia were less genitally and subjectively responsive to noncoital (oral sex) as well as coital visual sexual stimuli than women without s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 24 publications
(28 reference statements)
8
54
2
3
Order By: Relevance
“…In accordance with earlier research, the current findings show that women with vaginismus also distinguish themselves from controls with regard to their subjective (deliberate) global affective associations with sexual stimuli [30]. These findings underline the important role of ambivalent emotions in response to erotic stimuli in women with various sexual dysfunctions [13,47–49]. The current study in women with vaginismus showed that enhanced levels of more negative affect occurred not only in response to penetration stimuli but also following nonpenetration stimuli.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with earlier research, the current findings show that women with vaginismus also distinguish themselves from controls with regard to their subjective (deliberate) global affective associations with sexual stimuli [30]. These findings underline the important role of ambivalent emotions in response to erotic stimuli in women with various sexual dysfunctions [13,47–49]. The current study in women with vaginismus showed that enhanced levels of more negative affect occurred not only in response to penetration stimuli but also following nonpenetration stimuli.…”
Section: Discussionsupporting
confidence: 91%
“…The results for physiological sexual arousal in women with dyspareunia are somewhat mixed, with some research suggesting that women with dyspareunia have greater vasocongestion to depictions of coitus compared to healthy controls (Brauer, Laan, & ter Kuile, 2006), and other data showing the opposite pattern (Wouda et al, 1998). Although physiological sexual arousal was not directly measured in this study, the relationship between cognitive distraction and sexual arousal has clear implications for our results.…”
Section: Discussioncontrasting
confidence: 55%
“…Research conducted in laboratory settings indicates that there are no significant differences between women with vulvovaginal pain and non afflicted women relative to their physiological level of sexual arousal when exposed to an erotic stimulus, although women with pain tend to report more negative feelings toward the stimulus [13][14][15].…”
Section: Explanation To the Answers To Questionmentioning
confidence: 99%
“…Specifically, controlled studies have shown that they report significantly less sexual desire, arousal and satisfaction, more difficulty reaching orgasm, as well as lower frequencies of intercourse and more negative attitudes toward sexuality than pain-free controls [12]. Research conducted in laboratory settings indicates that there are no significant differences between women with vulvovaginal pain and non afflicted women relative to their physiological level of sexual arousal when exposed to an erotic stimulus, although women with pain tend to report more negative feelings toward the stimulus [13][14][15].…”
Section: A Psychological Sexual and Relationship Consequencesmentioning
confidence: 99%
See 1 more Smart Citation